Learning about the practice of nursing in the COVID-19 era - Velarde-Pacheco, Elsa Patricia (Universidad de Sonora, 2021)
For society, governments and health professionals, the COVID-19 pandemic has been very educational in many ways. In the first place, it has taught us that globalization, when understood and taken advantage of, can bring great benefits, but that it can have collateral effects such as the spread of a disease that can be lethal. Secondly, despite technological advances, the different health systems have not been able to contain the pandemic, and as a result of this situation, public health has become a priority.